Inhibitors of protein arginine deiminases and their efficacy in animal models of multiple sclerosis. Issue 9 (1st May 2017) - Sarswat, Amit; Wasilewski, Ewa; Chakka, Sai K.; Bello, Angelica M.; Caprariello, Andrew V.; Muthuramu, Chithra M.; Stys, Peter K.; Dunn, Shannon E.; Kotra, Lakshmi P.
Graphical abstract: Abstract: Protein arginine deiminases (PAD) are implicated in a variety of inflammatory and neurodegenerative diseases including multiple sclerosis (MS). Following the discovery of an in silico hit containing hydantoin and a piperidine moiety, we hypothesized that a 2-carbon linker on the hydantoin would be necessary for a 5-membered heterocycle for optimal PAD inhibitory activity. We designed thirteen compounds as potential inhibitors of PAD2 and PAD4 enzymes—two important PAD enzymes implicated in MS. Two compounds, one with an imidazole moiety (22 ) and the other with a tetrazole moiety (24 ) showed good inhibition of PAD isozymes in vitro and in the EAE mouse model of MS in vivo . Further experiments suggested that compound 22, a non-covalent inhibitor of PAD2 and PAD4, exhibits dose-dependent efficacy in the EAE mouse model and in the cuprizone-mediated demyelination model.